The Impact of Technology on the Social and Spiritual Lives of the Youth - Mandla Khumalo; Nonhlanhla Precious Dunn (Tinta Emas Publisher, 2026)
This study explored the impact of technology on the social and spiritual lives of the youth. Technology is advancing the daily activities for the youth and with such advancements comes certain impacts. Therefore this study tried to ascertain the benefits and negative effects of technology on the youth using an exploratory framework from an interpretive perspective. Semi-structured interviews were used as the primary source of data. Data was collected from participants who included both adults and young people. The youth were between the ages of 14 and 24. The adult participants were between the ages of 36 – 52 in range. The results revealed that technology has enhanced the social and spiritual lives of the youth through access to virtual sermons, access to spiritual music and has also broadened interaction channels without time and location barriers. On the negative side, the results show that the youth are becoming lazy and mostly relying on the internet for information and thus affecting their critical thinking ability. While technology can enhance the youth‟s learning capabilities through tailored approaches, excessive usage like prolonged screen time and prolonged social media engagements have a negative impact particularly on communication and academic performance.